Nematodal otitis by Stenurus globicephalae in a melon-headed whale (Peponocephala electra) stranded in Northeastern Brazil: case report and literature update - Hodias S. Oliveira Filho; José Lucas Costa Duarte; Raquel Mota Freitas Pereira; Pedro Lucas Jordão de Luna Araújo; Naftali Camily Fernandes de Lima; Raquel de Oliveira Simões; Bruno de Oliviera Telles Ferreira; Carlos Iberê Alves Freitas; Augusto Carlos da Bôaviagem Freire; Ana Bernadete Lima Fragoso; Flávio José de Lima Silva; Josué Díaz-Delgado; et al. (Veterinary Research Communications, 2026)
Cetaceans are highly adapted marine mammals whose survival depends on precise auditory and echolocation systems. Therefore, disease processes affecting these systems, including parasitic infections pose significant morbidity and may result in stranding and death. Here, we describe the pathologic and parasitological findings in an adult, male melon-headed whale ( Peponocephala electra ) stranded dead on the Brazilian coast. The main gross pathologic findings consisted of bilateral otitis media associated with numerous nematodes in the tympanic bullae that occluded the tympanic lumen and resulted in compression of the tympanic membrane. Other relevant gross findings were abdominal effusion, visceral congestion, pulmonary petechiae, and lack of ingesta. Histopathologic examination of the tympanic membrane and middle ear soft tissue revealed chronic otitis and myringitis with epithelial hyperplasia and multifocal ulceration with intralesional nematodes. These nematodes were morphologically identified as Stenurus globicephalae through direct microscopy and electron microscopy analyses. In this case, severe parasitism of the tympanic apparatus was considered the primary pathologic condition. We surmise that the severity of the lesions noted in the auditory system could have resulted in disorientation and stranding, and, together with the physiological stress response associated with live stranding, ultimately led to death in this individual. This report underscores the role of parasitic otitis caused by S. globicephalae as a differential etiological diagnosis for stranding and death in cetaceans along the Brazilian coast and provides an updated overview of the literature on otic parasitism in cetaceans.

Habitat-associated detection of Toxoplasma gondii and Sarcocystis spp. in Cetaceans from the Brazilian coast - Thalita Faita; Lara Borges Keid; Natalia Silvestre-Perez; Gláucia Pereira de Sousa; Geovana Carolaine Ramos Thomé; Beatriz de Magalhães Ceron; Samira Costa-Silva; Cristiane Kiyomi Miyaji Kolesnikovas; Pedro Volkmer de Castilho; Fernanda Loffler Niemeyer Attademo; Fábia de Oliveira Luna; Angélica Maria Sánchez-Sarmiento; et al. (Veterinary Research Communications, 2026)
Cetaceans are sentinels of marine ecosystem health and are increasingly exposed to protozoal pathogens. This study investigated the occurrence and molecular identity of Sarcocystidae protozoa in 159 stranded cetaceans representing 21 species along the Brazilian coast. Molecular analysis based on PCR amplification and sequencing of the sarcocystid internal transcribed spacer 1 (ITS1) region revealed infections in 14 individuals, showing a clear habitat-associated distribution. Toxoplasma gondii and Sarcocystis neurona were detected in nine coastal cetaceans, consistent with transmission from terrestrial definitive hosts via land-to-sea runoff. In contrast, a distinct Sarcocystis lineage consistently reported in cetaceans and pinnipeds was identified in six pelagic individuals. Analyses of mitochondrial cytochrome c oxidase subunit I and 18S rDNA markers revealed close similarity to species reported in avian definitive hosts, suggesting a life cycle involving marine or pelagic birds. This ecological segregation reflects differences in parasite transmission pathways and host–habitat interactions. This study provides the first report of S. neurona in Brazilian cetaceans and the first global record of this parasite in Guiana dolphin ( Sotalia guianensis ). Overall, these findings emphasize the role of habitat use in shaping infection patterns and reinforce the importance of a One Health framework to understand land–sea and potentially marine-specific pathogen transmission, as well as its implications for marine wildlife health and conservation.

Development of a multiplex real-time PCR assay for species-level identification within Aspergillus section Fumigati - Alexandre Mendonça; Ricardo Franco-Duarte; Cristina Veríssimo; Raquel Sabino; Paula Sampaio (Mycological Progress, 2026)

Association of Nepeta cataria L. essential oil and eugenol: synergism and safe anesthesia in tambaqui Colossoma macropomum (Cuvier, 1818) - Taissa Viana Damasceno; Thaysa de Sousa Reis; Axell Lins; Priscille Fidelis Hartcopff; Marcelo Victor dos Santos Brito; Daniella Rocha Bittencourt; Luiz Fernando Duarte de Andrade Junior; Alicia Chaves Manito; Gabriela de Paula Goyana; Cibely Camille Fernandes Ferreira; Dayanne Raquel de Sousa Barros; Luana Vasconcelos de Souza; et al. (Veterinary Research Communications, 2026)
Anesthetics are widely employed in aquaculture and in research environments utilizing fish as experimental models, with the aim of mitigating stress and hypermotility during handling procedures. Among the most commonly used anesthetic agents, eugenol stands out for its suitability across multiple species, enabling safer handling and transportation while minimizing physiological impact on the animals. For the experimental procedure, three oil mixtures were prepared in a 1:1 ratio. The first contained 50% eugenol and 50% Nepeta cataria essential oil (ENCO); the second mixture was 50% eugenol and 50% corn oil ( Zea mays ) (ECO); and the third was 50% Nepeta cataria essential oil and 50% corn oil (NCCO). The present study proposes a behavioral and electrophysiological assessment of Colossoma macropomum subjected to immersion baths containing different concentrations of Nepeta cataria L. 50% and eugenol 50%, in addition to investigating the underlying components of the synergism and the mechanism of action of eugenol. A total of 288 juvenile specimens, of mixed sex, with a mean body mass of 25.34 ± 3.2 g, were used. Experiment 1: assessed the synergistic potentiation between the compounds, based on latency times for anesthetic induction and recovery. Experiment 2: performed electrophysiological analyses of muscle (EMG) and cardiac (ECG) functions. Experiment 3: evaluated the influence of flumazenil on the activation of the anesthetic agents. Evaluations were conducted during 10-minute immersion baths at concentrations of 30 µL·L⁻¹, 35 µL·L⁻¹, 40 µL·L⁻¹, 45 µL·L⁻¹, and 50 µL·L⁻¹. The combination of Nepeta cataria essential oil and eugenol promotes good muscle relaxation and minor alterations in the cardiovascular system, promoting easily reversible bradycardia. The findings indicate that the combination of Nepeta cataria essential oil and eugenol constitutes a promising and safe alternative, due to the synergistic reduction in induction time and the maintenance of cardiac safety, which allowed for a reduction in the concentration required without compromising the maintenance of the anesthetic plane. Furthermore, flumazenil was found to exert a significant influence on both the induction process and the recovery phase of anesthesia.

Sustainable Production and In Vitro Giardicidal Activity of Bioactive Compounds Derived from Arthrospira Platensis - Ketyline Lira de Lima; Júlia Sofia Neves de Sousa; Karina Evelyn de Lima Albuquerque Santos; Maria Rafaele Oliveira Bezerra da Silva; Raquel Pedrosa Bezerra; Romero Marcos Pedrosa Brandão Costa; Kethylen Barbara Barbosa Cardoso; Patrícia Melo Ferreira; Genésio Florentino Duarte Neto; Silvana de Fátima Ferreira; Daniela de Araújo Viana Marques (Acta Parasitologica, 2026)
Background Giardiasis remains a globally prevalent neglected parasitic disease, and limitations associated with conventional therapies highlight the need for alternative and complementary strategies. In this context, microalgae biocompounds have emerged as promising sources of antiparasitic agents. Objective This study aims to evaluate the in vitro preliminary screening activity (vital dye exclusion). Methods Aqueous extracts of Arthrospira platensis obtained by different extraction methods, as well as the bioactivity of the product derived from in vitro digestion (PDV), aiming to assess the influence of extraction and digestive bioactivation on antiparasitic efficacy. Extracts were produced by magnetic stirring and sonication, followed by exposure of Giardia duodenalis cysts to increasing concentrations, with metronidazole used as a reference drug. The PDV was generated using a standardized simulated gastrointestinal digestion model. Sonicated extracts showed enhanced membrane damage compared to mechanically stirred extracts, consistent with improved release of intracellular bioactive compounds. The IC 50 values for the sonicated, agitated, and PDV samples were, respectively: 95,4; 153.1 and 43.6 μg/mL. Results The PDV demonstrated activity across multiple concentrations and, under comparable conditions, outperformed metronidazole. These findings suggest that digestive processing may increase the bioaccessibility of active moieties responsible for antiparasitic effects. Conclusions Overall, the results support A. platensis as a sustainable source of giardicidal biocompounds and highlight the relevance of physiologically relevant in vitro digestion models for predicting functional antiparasitic activity and guiding future translational research.

Metagenomic Insights Into Red Sea Biodiversity Across the Web of Life - Elisa Laiolo; Christopher A. Hempel; Balegh A. Abukabbos; Omar I. Abunayyan; Intikhab Alam; Taiba Alamoudi; Wejdan A. Alkhaldi; Zuhair M. Almubarak; Hamad A. Alnashri; Afrah Alothman; Tareq H. Alqahtani; Khalid A. Alshaikh; et al. (Environmental Microbiology, 2026)
Earth's biodiversity is central to ecosystem health and resilience, providing essential functions and services. The Red Sea is a recognised marine biodiversity hotspot with high endemism and unique environmental conditions that support extensive but poorly resolved biodiversity. Here, we applied metagenomic analyses to sediment samples collected from coastal to deep‐sea environments during the Red Sea Decade Expedition 2022 to characterise biodiversity across the web of life. From a single shotgun assay per sample, this approach simultaneously characterised the sediment microbiome, which amplicon‐based surveys recover only through parallel, targeted assays, and extended detection to higher eukaryotes. Using high‐throughput sequencing, we generated 12.8 billion sequences, revealing taxa covering all domains of life. Although eukaryotic sequences represented only 0.7% of the taxonomically annotated dataset, we managed to identify 679 eukaryotic families. Prokaryotic diversity was high, as expected in a basin‐scale sampling coupled with high sequencing depth, with groups covering a wide functional array. Community structure analyses revealed depth‐driven stratification of open‐ocean benthic microbial communities and latitudinal structuring of coastal benthic eukaryotes. Overall, this dataset provides an empirical reliability–coverage trade‐off with direct consequences for the design of eDNA monitoring programmes targeting conservation‐priority taxa, and clear priorities for taxa specific reference‐database expansion.

Land use controls the spatiotemporal patterns of surface water quality of the Quadrilátero Ferrífero mineral province, Brazil - Gabriel Soares de Almeida; Rafael Tarantino Amarante; Normara Yane Mar da Costa Andrade; Roberto Dall’Agnol; Prafulla Kumar Sahoo; Paulo Rógenes Monteiro Pontes; Emmanoel Vieira Silva-Filho; Eduardo Duarte Marques; Raquel Fernandes Mendonça; Abraão Gomes Soares Junior; Gabriel Negreiros Salomão (Environmental Geochemistry and Health, 2026)
Surface water quality in the Quadrilátero Ferrífero, a mining province in southeastern Brazil, was evaluated by combining water quality indices (WQI), land use and land cover (LULC), and population data to identify spatial and seasonal influences on river chemistry. We analyzed 835 (rainy) and 845 (dry) samples and calculated WQI scores using established methods from the literature. The methods for calculating the WQI detected broad signals of eutrophication and those related to sanitation but were less sensitive to inorganic and potentially toxic elements (PTE), whereas CCME, especially when including PTE variables, offered a more rigorous and adaptable assessment for mining-influenced areas. Microcatchments were classified into LULC groups based on the proportional dominance and co-occurrence of classes. Across methods and seasons, WQI values showed a clear degradation gradient aligned with increasing human activity. Catchments dominated by natural cover and low-intensity uses consistently exhibited the highest WQI values; notably, mining-influenced classes with substantial natural vegetation often clustered towards this higher-quality end. In contrast, catchments shaped by human occupation in urban and rural settings showed the lowest WQI scores and were statistically distinct from the low-intensity group in most pairwise comparisons, although overlaps occurred among the anthropogenic classes depending on method and season. Total population per micro-catchment was inversely related to WQI results by IGAM method in both seasons, highlighting the impact of urban expansion and infrastructure pressures on water-quality decline. Overall, the LULC-based microcatchment classification was crucial for understanding how dominant land use patterns influence water quality and for guiding targeted watershed management in mining regions.

Himatanthus drasticus (Mart.) Plumel (APOCYNACEAE): phytochemical profile, evaluation of antibacterial and drug-potentiating activity, and toxicity of stem bark extracts - Maraiza Gregorio de Oliveira; Adrielle Rodrigues Costa; Jailson Renato de Lima Silva; Carlos Alonso leite dos Santos; Ana Raquel Pereira da Silva; Daniel Sampaio Alves; José Weverton Almeida-Bezerra; Ademar Maia Filho; José Walber Gonçalves Castro; Bárbara Fernandes Melo; Francisca de Fátima Silva de Sousa; Marcos Santos; et al. (Vegetos, 2026)

Biopolymer-based strategies to improve delivery properties of B12 in alginate gels: Role of protein fillers and chitosan - Raquel de Freitas Agondi; Ludmila Meskelis; Larissa Graziele Rauber Duarte; Ana Carla Kawazoe Sato; Carolina Siqueira Franco Picone (Food Bioscience, 2026)

Zinc and circulating microRNAs in women with insulin resistance - Danielle Caroline da Silva Dias; Graziela Biude Silva Duarte; Leonam da Silva Pereira Batista; Marcelo Macedo Rogero; Fernando Barbosa; Silvia Maria Franciscato Cozzolino; Raquel Costa Silva Dantas-Komatsu; Karina Zaira Silva Marinho Costa; Bruna Zavarize Reis (Journal of Trace Elements in Medicine and Biology, 2025)

Hydrogeochemical process, evaluation of pollution source apportionment and baseline characteristics of surface water in the Quadrilátero Ferrífero, Minas Gerais, Brazil - Gabriel Soares de Almeida; Gabriel Negreiros Salomão; Roberto Dall'Agnol; Rafael Tarantino Amarante; Lúcio Cardoso de Medeiros Filho; Prafulla Kumar Sahoo; Paulo Rógenes Monteiro Pontes; Emmanoel Vieira Silva-Filho; Eduardo Duarte Marques; Lucas Pereira Leão; Raquel Fernandes Mendonça; Abraão Gomes Soares Junior (Journal of Geochemical Exploration, 2025)

Cultural contrasts in vegan food choice: A multi-methods comparative analysis of consumption values in Portugal and India - Paulo Duarte; Raquel Meneses; Susana C. Silva; Riya Roy Tharakan (International Journal of Gastronomy and Food Science, 2025)

Essential oil emulsions as a strategy to inhibit Aspergillus flavus and aflatoxin production in maize - Naara Aparecida Almeida; Daniel Lucino Silva dos Santos; Raquel Costa Chevalier; Isabelle Dias Vieira; Aildson Pereira Duarte; Rosiane Lopes Cunha; Liliana de Oliveira Rocha (Food Bioscience, 2025)

Beneficial Use of Marine Gypsum in Cantaloupe Culture and its Environmental Impact on Sandy Soil - Maria Valdete da Costa; José Francismar de Medeiros; Ana Kaline da Costa Ferreira; Paula Romyne de Morais Cavalcante Neitzke; Cíntia Raquel Duarte de Freitas; Fernando Henrique Alves da Silva; Eveline de Almeida Ferreira; Diana Ferreira de Freitas; Jessica Crhistie de Castro Granjeiro; Rita Oliveira Magally da Silva Marcelino; Luiz Fernando de Sousa Antunes; Rafael Oliveira Batista; et al. (Journal of Soil Science and Plant Nutrition, 2025)

The biological potential and health-benefits of flavonoids: A review and development opportunities - Marco Duarte; Sílvia Santos Pedrosa; P Raaj Khusial; Ana Raquel Madureira (Chemico-Biological Interactions, 2025)

Conversion of brewery spent grain into 2,3-butanediol: A sustainable approach using biomass treatments - Daniele Misturini Rossi; Estela Marisutti; Clarissa Izabel Silveira Costa; Estela Moschetta Eidelwein; Bruno Marques Viegas; Lilian Raquel Hickert; Suse Botelho da Silva; Lovaine Silva Duarte; Marco Antônio Záchia Ayub (Journal of Environmental Chemical Engineering, 2025)

Feline botulism: two decades and two reports - Ísis Assis Braga; Nicoly Ferreira de Urzedo; Guilherme Oliveira Maia; Ana Paula Carvalho Gomes; Raiany Borges Duarte; Bruna Samara Alves-Ribeiro; Andressa da Silva Martins; Tamires Ataides Silva; Luiz Henrique Barbosa Pires; Stéfanne Rodrigues Rezende; Nathalia de Assis Pereira; Raquel Loren dos Reis Paludo; et al. (Veterinary Research Communications, 2025)

Spatial distribution, potential sources and geochemical baseline of Fe and potentially toxic elements in stream sediments in Quadrilátero Ferrífero, Brazil - Lucio Cardoso de Medeiros Filho; Gabriel Negreiros Salomão; Roberto Dall’Agnol; Gabriel Soares de Almeida; Rafael Tarantino Amarante; Prafulla Kumar Sahoo; José Tasso Felix Guimarães; Emmanoel Vieira da Silva Filho; Eduardo Duarte Marques; Lucas Pereira Leão; Raquel Fernandes Mendonça; Abraão Gomes Soares Junior (Applied Geochemistry, 2025)

Parietal Intradiploic meningoencephalocele: a case presenting with focal neurological deficits - Raquel Falcão de Freitas; Filipa Ferreira de Oliveira; Isa Duarte Barbosa; Leopoldina Pereira; Guilherme Bastos Silva; Filiation (Acta Neurologica Belgica, 2025)

Novel paramyxovirus in wild pinnipeds, Brazil - Samira Costa-Silva; Ana Carolina Ewbank; Aricia Duarte-Benvenuto; Carlos Sacristán; Rodrigo M. Soares; Angélica M. Sánchez-Sarmiento; Natália Silvestre-Perez; Pedro Volkmer Castilho; Cristiane K. M. Kolesnikovas; Caroline Freitas Pessi; Rafael Sardinha Murro; Carla B. Barbosa; et al. (Veterinary Research Communications, 2025)
Most emerging zoonotic viral infections originate in wildlife. The Paramyxoviridae and Coronaviridae families are important in terms of zoonotic potential and diversity of host susceptibility. To date, the only paramyxoviruses described in pinnipeds are within the genus Morbillivirus . An alphacoronavirus has been reported in pinnipeds. Herein, we surveyed for Paramyxoviridae and Coronaviridae in 46 animals of four pinniped species stranded along the coasts of Santa Catarina and São Paulo states, Brazil, between 2016 and 2022. A novel paramyxovirus (family Paramyxoviridae ) was detected in an Antarctic fur seal ( Arctocephalus gazella ) and in two South American fur seals ( Arctocephalus australis ). The sequences presented with less than 83% amino acid identity to the closest published paramyxovirus sequences, amplified in Microchiroptera sp. in Vietnam and in Asiatic yellow bats ( Scotophilus kuhlii ) in Cambodia. Phylogenetic analysis of the paramyxovirus sequences clustered into the genus Jeilongvirus . Gross and histopathological analyses did not identify any related lesions and the viral zoonotic potential is unknown. None of the animals were PCR-positive to coronavirus. To our knowledge, this is the first report of paramyxovirus infection in pinnipeds in Brazil and the first paramyxovirus not classified as Morbillivirus in seals, sea lions and walruses. To better understand the natural history of this novel virus, future pathological, serological, and molecular studies based on pan- Paramyxoviridae RT-PCRs are recommended.

Assessing the vulnerability of urban tree species to climate change: The case study of Lisbon gardens - Ana Raquel Cunha; Ana Luísa Soares; Sílvia Catarino; Maria Cristina Duarte; Maria M. Romeiras (Urban Forestry & Urban Greening, 2025)

Selenium biomarkers and miR‐7‐5p in overweight/obese women - Higor Paiva de Mendonça Alves; Graziela Biude Silva Duarte; Adriano Carlos de Souza Junior; Leonam da Silva Pereira Batista; Marcelo Macedo Rogero; Fernando Barbosa Jr; Silvia Maria Franciscato Cozzolino; Raquel Costa Silva Dantas-Komatsu; Karina Zaira Silva Marinho Costa; Bruna Zavarize Reis (Journal of Trace Elements in Medicine and Biology, 2024)

Biotechnological potential of actinomycetes in the 21st century: a brief review - Rafael de Souza Rodrigues; Antonia Queiroz Lima de Souza; Maria Divina Oliveira Feitoza; Thalita Caroline Lima Alves; Anderson Nogueira Barbosa; Sarah Raquel Silveira da Silva Santiago; Afonso Duarte Leão de Souza (Antonie van Leeuwenhoek, 2024)

Pharmacological Evidence of Eugenia Brasiliensis Leaves in a Reserpine-Induced Fibromyalgia Model: Antinociceptive, Emotional, Anti-Inflammatory, and Neurotrophic Effects - Scheila Iria Kraus; Jeane Bachi Ferreira; Angela Patricia França; Vinícius Alexandre Wippel; Rodrigo Bainy Leal; Raquel Oppermann; Michele Debiasi Alberton; Morgana Duarte da Silva (Molecular Neurobiology, 2024)

Application of the galactomannan gel from Cassia grandis seeds for biomedical purposes: Study of the incorporation of collagenases and their release profile - Carolina de Albuquerque Lima Duarte; Mateus Gonçalves da Silva; Ana Lúcia Figueiredo Porto; Maria Carolina de Albuquerque Wanderley; Sabrina Swan Souza da Silva; Alexsandra Frazão de Andrade; Raquel Pedrosa Bezerra; Attilio Converti; Diego Gomes Ramos; Daniela de Araújo Viana Marques; Priscilla Barbosa Sales de Albuquerque (Carbohydrate Polymers, 2024)

Fibrinonecrotic enteritis and orchitis associated with Salmonella enterica subsp houtenae infection in a short-tailed boa (Boa constrictor amarali) - Raquel M. de Freitas Pereira; Hodias S. de Oliveira Filho; José L. C. Duarte; Fabiano R. P. Júnior; Telma de Sousa Lima; Kin M.O.L. dos Santos; Edivaldo da Silva Pereira; Nádyra Jerônimo da Silva; Celso J. Bruno de Oliveira; Jeann Leal de Araújo; Fábio de Souza Mendonça (Journal of Comparative Pathology, 2024)

New approaches for modulation of alginate-chitosan delivery properties - Ludmilla Meskelis; Raquel F. Agondi; Larissa G.R. Duarte; Matheus D. de Carvalho; Ana Carla K. Sato; Carolina S.F. Picone (Food Research International, 2024)

Evidence of hawksbill turtle (Eretmochelys imbricata) depredation on fish caught in gillnets - Yusuf C. El-Khaled; Carlos M. Duarte; Raquel S. Peixoto (Frontiers in Marine Science, 2023)
Bycatch is a major global threat to marine megafauna and occurs in nearly all fishing fleets, including small-scale fisheries that use gillnets. Gillnets represent a threat to endangered air-breathing megafauna, who incidentally entangle in bottom-set gillnets and suffocate after being attracted by bait that is secured on fishing gear. We here provide the first evidence that hawksbill turtles feed on trapped fish in gillnets, suggesting that potential prey items trapped in gillnets may act as additional bait, attracting carnivorous sea turtles towards this threat. This overlooked depredating behaviour potentially explains and increases the likelihood of critically endangered hawksbill turtle bycatch in gillnet fisheries, calling for technological and management solutions.

Probiotics mitigate thermal stress- and pathogen-driven impacts on coral skeleton - Mahdi Moradi; Phillipe R. Magalhaes; Raquel S. Peixoto; Cassia C.A.C. Jonck; Daniel François; Anna Clara F. Bellot; Jonatã B. Teixeira; Carla S. Silveira; Gustavo Duarte; Heitor Evangelista; Catia F. Barbosa (Frontiers in Marine Science, 2023)
Threats leading to a reduction in coral populations are apparent worldwide. Several different approaches have been tested to accelerate the adaptation of corals to a changing climate. Here, we evaluated the skeleton structure, crystal habit, and chemical changes of the coral Pocillopora damicornis in response to the pathogen ( Vibrio coralliilyticus ) and probiotic (Beneficial Microorganisms for Corals, BMCs) inoculation under ambient conditions (26 °C) and thermal stress (30 °C) during a 50-day mesocosm experiment. The skeletons were analyzed using microtomography, energy-dispersive x-ray spectroscopy (EDX/SEM), and densitometry to investigate the skeleto-physico-chemical micro-morphological changes in porosity, median pore-size diameter, crystal habit, Mg/Ca, Sr/Ca, the skeleton mineral density (g/cm 2 ) and skeleton mineral content (g –2 ). The results indicate considerable changes in the coral skeleton caused by both temperature and microbial inoculation. Most importantly, lower density (to ∼ x̄ 0.5 g/cm 2 ) and higher porosity (up to ∼ x̄ 47%) were correlated with inoculation of V. coralliilyticus and mitigated by probiotics. BMCs also substantially increased calcification, as evidenced by Mg/Ca in the skeleton of thermally stressed corals. At the micron scale, aragonite crystal fibbers precipitated during the experiments showed an acicular habit in thermally stressed and pathogen-inoculated corals kept at 30 °C. In contrast, a spherulitic habit, characteristic of high growth rates, was observed in corals inoculated with both BMCs and V. coralliilyticus . Our findings reveal that pathogen inoculation and thermal stress had notable impacts on coral skeleton properties, including porosity, density, and crystal morphology, in a short period of time, which highlights the potential impacts of shifts in climate warming and environmental quality. Interestingly, BMCs played a role in maintaining the properties of skeleton calcification.

Therapeutic action of the ethanolic extract of Platonia insignis Mart. leaves on induced respiratory distress syndrome in rats - Maria Lanna Souza da Silva; Penina Sousa Mourão; Vitória Raquel da Silva Reis; Clara Andrezza Crisóstomo Bezerra Costa; Orlando Francisco da Silva Moura; Rodrigo de Araujo Moreira; Johnnatan Duarte de Freitas; Sâmya Danielle Lima de Freitas; Rosemarie Brandim Marques; José Figueredo-Silva; Danniel Cabral Leão Ferreira; Valdiléia Teixeira Uchôa; et al. (South African Journal of Botany, 2023)

Phenological dynamics of four populations of Handroanthus spongiosus in seasonally dry tropical forest in Brazil - Jailton de Jesus Silva; Edson Ferreira Duarte; Lúcia Helena Piedade Kiill; Raquel Araujo Gomes; Bárbara França Dantas; Claudineia Regina Pelacani; Ligia Silveira Funch (Flora, 2023)

Potential of bioactive molecules from photosynthetic microorganisms on Leishmania spp.: A review - Sabrina Swan Souza da Silva; Alexsandra Frazão de Andrade; Milena de Paiva-Cavalcanti; João Carlos Monteiro de Carvalho; Daniela de Araújo Viana-Marques; Carolina de Albuquerque Lima Duarte; Ana Lúcia Figueiredo Porto; Raquel Pedrosa Bezerra (Algal Research, 2023)

Proteostasis networks in aging: novel insights from text-mining approaches - Diogo Neves; Sara Duarte-Pereira; Sérgio Matos; Raquel M. Silva (Biogerontology, 2023)
Aging is a topic of paramount importance in an increasingly elderly society and has been the focus of extensive research. Protein homeostasis (proteostasis) decline is a hallmark in aging and several age-related diseases, but which specific proteins and mechanisms are involved in proteostasis (de)regulation during the aging process remain largely unknown. Here, we used different text-mining tools complemented with protein–protein interaction data to address this complex topic. Analysis of the integrated protein interaction networks identified novel proteins and pathways associated to proteostasis mechanisms and aging or age-related disorders, indicating that this approach is useful to identify previously unknown links and for retrieving information of potential novel biomarkers or therapeutic targets.

Full genotype characterization of Brazilian canine G3P[3] strains during a 10-year survey (2012–2021) of rotavirus infection in domestic dogs and cats - Lais Sampaio Azevedo; Fernanda Faria Costa; Monique Beerens Abdul Ghani; Ellen Viana; Yasmin França; Roberta Salzone Medeiros; Raquel Guiducci; Simone Guadagnucci Morillo; Dieli Primo; Ricardo Duarte Lopes; Michele Soares Gomes-Gouvêa; Antonio Charlys da Costa; et al. (Archives of Virology, 2023)

Evaluating the in vitro digestion of lipids rich in medium-chain fatty acids (MCFAs) using dynamic and static protocols - Ericsem Pereira; Jean-Michel Fernandes; Raquel Gonçalves; Ana C. Pinheiro; M. Salomé Duarte; M. Madalena Alves; Antonio J.A. Meirelles; Guilherme J. Maximo; Antonio A. Vicente (Food Chemistry, 2023)

Editorial: Emerging Topics in Coastal and Transitional Ecosystems: Science, Literacy, and Innovation - Bernardo Duarte; Célia M. Teixeira; Irene Martins; Aschwin H. Engelen; Raquel L. Costa; Janine Barbara Adams; Maria João Bebianno; Ricardo A. Melo; Vanessa F. Fonseca (Frontiers in Marine Science, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Plant growth–promoting traits of yeasts isolated from the tank bromeliad Vriesea minarum L.B. Smith and the effectiveness of Carlosrosaea vrieseae for promoting bromeliad growth - Andréa R. Marques; Alessandra A. Resende; Fátima C. O. Gomes; Ana Raquel O. Santos; Carlos A. Rosa; Alexandre A. Duarte; José Pires de Lemos-Filho; Vera Lúcia dos Santos (Brazilian Journal of Microbiology, 2021)

Acarbose presents in vitro and in vivo antileishmanial activity against Leishmania infantum and is a promising therapeutic candidate against visceral leishmaniasis - Rafaella R. Costa; João A. Oliveira-da-Silva; Thiago A. R. Reis; Grasiele S. V. Tavares; Débora V. C. Mendonça; Camila S. Freitas; Daniela P. Lage; Vívian T. Martins; Luciana M. R. Antinarelli; Amanda S. Machado; Raquel S. Bandeira; Fernanda Ludolf; et al. (Medical Microbiology and Immunology, 2021)

Water and socioeconomic dependencies: a multiregional model - Miguel A. Almazán-Gómez; Rosa Duarte; Raquel Langarita; Julio Sánchez-Chóliz (Clean Technologies and Environmental Policy, 2021)

Anatomical changes and cytogenetic stability in bird of paradise plants after zygotic embryo cryopreservation by desiccation method - Júnia Rafael Mendonça Figueiredo; Patrícia Duarte de Oliveira Paiva; Diogo Pedrosa Corrêa da Silva; Renato Paiva; Raquel Mesquita; Rafaela Ribeiro Souza; Michele Valquíria dos Reis (In Vitro Cellular & Developmental Biology - Plant, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The Impact of Water from Sand Pit Lakes on Plant Growth, Soil, and Leachate - Fernanda Figueiredo Granja Dorilêo Leite; Guilherme Kangussu Donagemma; Paulo César Teixeira; Raquel Andrade Donagemma; Ana Carolina Barbosa do Canto; Fabiano de Carvalho Balieiro; Gabriel Souza Martins; Leonardo Duarte Batista da Silva (Water, Air, & Soil Pollution, 2020)

Evaluation of a cattle rapid test for early pregnancy diagnosis in sheep - Camila de Miranda e Silva Chaves; Ricardo Lopes Dias da Costa; Keila Maria Roncato Duarte; Renato Travassos Beltrame; Celia Raquel Quirino (Tropical Animal Health and Production, 2020)

Failure to complete treatment for latent tuberculosis infection in Portugal, 2013–2017: geographic-, sociodemographic-, and medical-associated factors - Alexis Sentís; Paula Vasconcelos; Rita Sá Machado; Joan A. Caylà; Mònica Guxens; Vasco Peixoto; Raquel Duarte; Isabel Carvalho; Carlos Carvalho (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Heat Waves Are a Major Threat to Turbid Coral Reefs in Brazil - Gustavo A. S. Duarte; Helena D. M. Villela; Matheus Deocleciano; Denise Silva; Adam Barno; Pedro M. Cardoso; Caren L. S. Vilela; Phillipe Rosado; Camila S. M. A. Messias; Maria Alejandra Chacon; Erika P. Santoro; Daniele B. Olmedo; et al. (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Environmental impact of the on-road transportation distance and product volume from farm to a fresh food distribution center: a case study in Brazil - Gilson Tristão Duarte; Irenilza de Alencar Nääs; Cláudio Monico Innocencio; Alexandra Ferreira da Silva Cordeiro; Raquel Baracat Tosi Rodrigues da Silva (Environmental Science and Pollution Research, 2019)

Mining leachate contamination and subfecundity among women living near the USA–Mexico border - Raquel Rivera Carvajal; Hector Duarte-Tagles; Álvaro J. Idrovo (Environmental Geochemistry and Health, 2019)

Higher contribution of globally rare bacterial taxa reflects environmental transitions across the surface ocean - Clara Ruiz‐González; Ramiro Logares; Marta Sebastián; Mireia Mestre; Raquel Rodríguez‐Martínez; Martí Galí; Maria Montserrat Sala; Silvia G. Acinas; Carlos M. Duarte; Josep M. Gasol (Molecular Ecology, 2019)
Microbial taxa range from being ubiquitous and abundant across space to extremely rare and endemic, depending on their ecophysiology and on different processes acting locally or regionally. However, little is known about how cosmopolitan or rare taxa combine to constitute communities and whether environmental variations promote changes in their relative abundances. Here we identified the Spatial Abundance Distribution (SpAD) of individual prokaryotic taxa (16S rDNA‐defined Operational Taxonomic Units, OTUs) across 108 globally‐distributed surface ocean stations. We grouped taxa based on their SpAD shape (“normal‐like”‐ abundant and ubiquitous; “logistic”‐ globally rare, present in few sites; and “bimodal”‐ abundant only in certain oceanic regions), and investigated how the abundance of these three categories relates to environmental gradients. Most surface assemblages were numerically dominated by a few cosmopolitan “normal‐like” OTUs, yet there was a gradual shift towards assemblages dominated by “logistic” taxa in specific areas with productivity and temperature differing the most from the average conditions in the sampled stations. When we performed the SpAD categorization including additional habitats (deeper layers and particles of varying sizes), the SpAD of many OTUs changed towards fewer “normal‐like” shapes, and OTUs categorized as globally rare in the surface ocean became abundant. This suggests that understanding the mechanisms behind microbial rarity and dominance requires expanding the context of study beyond local communities and single habitats. We show that marine bacterial communities comprise taxa displaying a continuum of SpADs, and that variations in their abundances can be linked to habitat transitions or barriers that delimit the distribution of community members.

The influence of meteorological parameters on Alternaria and Cladosporium fungal spore concentrations in Beja (Southern Portugal): preliminary results - Elsa Almeida; Elsa Caeiro; Ana Todo-Bom; Raquel Ferro; Ana Dionísio; Ana Duarte; Luiz Gazarini (Aerobiologia, 2018)

Composition and leishmanicidal activity of the essential oil of Vernonia polyanthes Less (Asteraceae) - Raquel Regina Duarte Moreira; Gilmarcio Zimmermann Martins; Raquel Varandas; Juliana Cogo; Caio Humberto Perego; Giovana Roncoli; Maria do Céu Sousa; Celso Vataru Nakamura; Lígia Salgueiro; Carlos Cavaleiro (Natural Product Research, 2017)

Potentiation of Paclitaxel-Induced Pain Syndrome in Mice by Angiotensin I Converting Enzyme Inhibition and Involvement of Kinins - Indiara Brusco; Cássia Regina Silva; Gabriela Trevisan; Camila de Campos Velho Gewehr; Flávia Karine Rigo; Lidia La Rocca Tamiozzo; Mateus Fortes Rossato; Raquel Tonello; Gerusa Duarte Dalmolin; Daniela de Almeida Cabrini; Marcus Vinícius Gomez; Juliano Ferreira; et al. (Molecular Neurobiology, 2017)

Cloning, Characterization, and Expression Levels of the Nectin Gene from the Tube Feet of the Sea Urchin Paracentrotus Lividus - Duarte Toubarro; Analuce Gouveia; Raquel Mesquita Ribeiro; Nélson Simões; Gonçalo da Costa; Carlos Cordeiro; Romana Santos (Marine Biotechnology, 2016)

Annual benthic metabolism and organic carbon fluxes in a semi-enclosed Mediterranean bay dominated by the macroalgae Caulerpa prolifera - Sergio Ruiz-Halpern; Raquel Vaquer-Sunyer; Carlos M. Duarte (Frontiers in Marine Science, 2014)

Experimental Evaluation of the Response of Coastal Mediterranean Planktonic and Benthic Metabolism to Warming - Raquel Vaquer-Sunyer; Carlos M. Duarte (Estuaries and Coasts, 2013)

Temperature Dependence of Oxygen Dynamics and Community Metabolism in a Shallow Mediterranean Macroalgal Meadow (Caulerpa prolifera) - Raquel Vaquer-Sunyer; Carlos M. Duarte; Gabriel Jordà; Sergio Ruiz-Halpern (Estuaries and Coasts, 2012)

Experimental evaluation of planktonic respiration response to warming in the European Arctic Sector - Raquel Vaquer-Sunyer; Carlos M. Duarte; Rocío Santiago; Paul Wassmann; Marit Reigstad (Polar Biology, 2010)

Submarine Groundwater Discharge to the Coastal Environment of a Mediterranean Island (Majorca, Spain): Ecosystem and Biogeochemical Significance - Gotzon Basterretxea; Antonio Tovar-Sanchez; Aaron J. Beck; Pere Masqué; Henry J. Bokuniewicz; Ruth Coffey; Carlos M. Duarte; Jordi Garcia-Orellana; Esther Garcia-Solsona; Lorena Martinez-Ribes; Raquel Vaquer-Sunyer (Ecosystems, 2010)

Sulfide exposure accelerates hypoxia‐driven mortalit - Raquel Vaquer-Sunyer; Carlos M. Duarte (Limnology and Oceanography, 2010)
The effect of the presence of sulfide on the survival of benthic organisms under hypoxia was tested using a meta‐analysis of published experimental results evaluating the effects of the presence of hydrogen sulfide on the median survival time of benthic macrofauna under hypoxia. The meta‐analysis confirmed that survival times under hypoxia are reduced by an average of 30% in marine benthic communities exposed to hydrogen sulfide. The effect of sulfide on survival was higher for egg forms than for juvenile or adult stages. The aggravation of the negative effects of spreading hypoxia in the presence of sulfide suggests that the threats derived from hypoxia to marine biodiversity are greater than anticipated on the basis of the direct effects of low oxygen concentration alone.

Ecosystem thresholds with hypoxia - Daniel J. Conley; Jacob Carstensen; Raquel Vaquer-Sunyer; Carlos M. Duarte (Hydrobiologia, 2009)

Xylitol production by Debaryomyces hansenii in brewery spent grain dilute-acid hydrolysate: effect of supplementation - Florbela Carvalheiro; Luís C. Duarte; Raquel Medeiros; Francisco M. Gírio (Biotechnology Letters, 2007)

A case of eumycetoma due to Madurella grisea in northern Brazil - Raquel Vilela; Olga M. V. Duarte; Carlos A. Rosa; Joao G. F. Castro; Sandra Lyon; Roberta L. Motta; Ana C. L. Moura (Mycopathologia, 2004)

The relative contribution of individual polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzo-p-furans (PCDFs) to toxic equivalent values derived for bulked human adipose tissue samples from Wales, United Kingdom - Raquel Duarte-Davidson; Stuart J. Harrad; Susan Allen; Andrew S. Sewart; Kevin C. Jones (Archives of Environmental Contamination and Toxicology, 1993)